Minimum fluidization velocity of binary mixtures of medium particles in the Air Dense medium fluidized bed. (2nd November 2019) - Fu, Zhijie; Zhu, Jesse; Barghi, Shahzad; Zhao, Yuemin; Luo, Zhenfu; Duan, Chenlong
Highlights: Minimum fluidization velocity of binary mixture of Geldart B/D particles was studied. The Umf of magnetite mixed with sand/gangue/coal were tested for coal beneficiation. A new correlation was developed for the prediction of Umf of binary systems. The correlation was based on the Cheung equation considering the particle size effect. Abstract: Minimum fluidization velocity of binary mixtures is one of the most important parameters when applying an Air Dense Medium Fluidized Bed for dry coal beneficiation. Measurements of minimum fluidization velocities were carried out for binary mixtures of magnetite and sand/gangue/coal particles. The experimental results showed that the minimum fluidization velocity of binary mixtures remained almost unchanged when the volume fraction of magnetite particles was above 50%, whereas it varied significantly when the volume fraction of magnetite particles was below 50%. A general correlation based on the Cheung equation has been developed for predicting the minimum fluidization velocity of binary mixtures in terms of particle size ratio, volumetric composition and incipient fluidization velocity of each component. The extended Cheung equation is in reasonable agreement with almost all the available experimental data in the present work and the literature, and it can be used to estimate accurately the minimum fluidization velocity of binary mixtures of medium particles for the ADMFB and other similar fluidized bed operations.